The Role of Para-Aortic Lymphadenectomy in the Surgical Staging of Women with Intermediate and High-Risk Endometrial Adenocarcinomas - Taymaa May (International Journal of Surgical Oncology, 2013)
Objectives. To characterize clinical outcomes in patients with intermediate or high-risk endometrial carcinoma who underwent surgical staging with or without para-aortic lymphadenectomy. Methods. This is a retrospective cohort study of patients with intermediate or high-risk endometrial adenocarcinoma who underwent surgical staging with (PPALN group) or without (PLN) para-aortic lymphadenectomy. Data were collected, Kaplan-Meier curves were generated, and univariate and multivariate analyses performed to compare differences in adjuvant therapy, disease recurrence, disease-free survival (DFS), and overall survival (OS). Results. 118 patients were included in the PPALN group and 139 in the PLN group. Patients in the PPALN group were more likely to receive adjuvant vaginal brachytherapy (25.4% versus 11.5%, OR=2.5, P=0.03) and less likely to receive adjuvant multimodal combination therapy (17.81% versus 28.8%, OR=0.28, P=0.002). DFS was improved in the PLN group as compared to PPALN (80% versus 62%, P=0.02). OS was equivalent (P=0.93). Patients in the PPALN group who had less than 10 para-aortic nodes removed were twice as likely to recur than patients who had 10 or more para-aortic nodes or patients in the PLN group (HR 2.08, CI 1.20–3.60, P=0.009). Conclusions. Patients in the PLN group were more likely to receive multimodal adjuvant therapy and had better DFS than the PPALN group. Pelvic lymphadenectomy followed by adjuvant radiation and chemotherapy may represent an effective treatment option for patients with intermediate or high-risk disease. If systematic para-aortic lymphadenectomy is performed and less than 10 para-aortic lymph nodes are obtained, multimodality adjuvant therapy should be considered to improve DFS.